Cross section measurement of the 191Ir(n,2n)190Ir reaction - Kalamara, A.; Vlastou, R.; Kokkoris, M.; Patronis, N.; Serris, M.; Stamatopoulos, A.; Chasapoglou, S.; Lagoyannis, A.; Harissopulos, S. (HNPS Advances in Nuclear Physics, 2019)
The cross section of the 191Ir(n,2n) reaction was experimentally determined relative to the 27Al(n,α)24Na reference reaction one, for incident neutron beam energies ranging from 15.3 to 20.9 MeV, by means of the activation technique. The quasi-monoenergetic neutron beams were produced at the 5.5 MV Tandem Accelerator ofNCSR "Demokritos" via the 3H(d,n)4He reaction. Following the irradiations the activity induced by the neutron beam at the targets and reference foils was measured by HPGe detectors. The cross sections for the population of the second isomeric state (m2) of 190Ir and the sum of the ground and isomeric states (g+m1+0.086 m2) were independently determined. Additionally, theoretical calculations of the above cross sections were carried out using the EMPIRE code. The details of these calculations concerning the optical model parameters, are described in the present work.